The IMMUNOMODULATORY EFFECT OF ENDURANCE EXERCISE (EE) AND RESISTANCE EXERCISE (RE) THROUGH THE KYNURENINE PATHWAY IN HEALTHY AND CANCER SUBJECT - Sienny Muliaty Sumali; Marta Wangsadinata Wong; Ireene Hillary Artauli Sinurat; Indira Vidiari Juhanna; I Putu Adiartha Griadhi (Sport and Fitness Journal, 2023)
ABSTRACT Introduction: Kynurenine pathway is a process that breaks down tryptophan, an amino acid found in many foods. One of the products of this pathway is kynurenine, which has been shown to affect the immune system.Acute and resistance exercise can alter the kynurenine pathway and enhance immune function by modifying immune cell mediators. Methods: This systematic review analyzed the effects of acute and resistance exercise on the kynurenine pathway and immune system. The study collected information through a computerized publication database search using specific text words and MeSH-Terms, limited to original articles published in English between 2016-2021. Results: From 10 clinical trials were summarized Exercise influences the kynurenine pathway and immune system, according to three studies acute and chronic endurance training in healthy patients resulted in higher kyn clearance and lower kyn levels. And two studies through a reduction in kyn levels and a downregulation of the kynurenine tryptophan ratio, cancer patients can modify their immune systems. Meanwhile one study had no effect on kyn levels in depressed patients who had undergone both short-term and long-term endurance and strength training. One study had increased their levels of kyn and their kyn:trp ratio. One study examined the short-term impacts of resistance and endurance training found that both types of exercise increased the expression of increase in CD3+ lymphocytes after both EE and RE and an increase in PD-1+ CD8+ T-cells after EE. Proportions of T-cell populations changed only after EE but without explicitly examining metabolites of the kynurenine pathway. Conclusion: By changing immune cell mediators, endurance exercise (EE) and resistance exercise (RE) can affect the kynurenine pathway and improve immunological function. Exercise therapies can result in cancer patients having lower levels of kynurenine and higher levels of tryptophan and kynurenic acid, both of which are linked to enhanced immune function and decreased inflammation. According to this research, exercise can be a non-pharmacological intervention to improve immune function and possibly prevent chronic illnesses linked to inflammation and immunological dysfunction. Keywords : physical activity, Exercise,aging, immunosenescence, innate immune system, adaptive immune system